Raking Process for Powder Bed Fusion of Ti–6Al–4V Alloy Powder Analyzed by Discrete Element Method - Okugawa, Masayuki; Isono, Yusuke; Koizumi, Yuichiro; Nakano, Takayoshi (MATERIALS TRANSACTIONS, 2023)
In order to avoid the formation of defects in additive manufacturing (AM) by powder bed fusion (PBF) process, it is crucial to understand the relationship between the quality of powder bed and a powder spreading process. In this study, the influences of conditions of powder raking process on the densities and homogeneity of powder bed have been examined by computer simulation using Discrete Element Method (DEM) and experiment of powder bed formation using a blade-type spreader for Ti–6Al–4V powder by way of example. The results were analyzed with a special focus on the effects of the relative size of powder particles with respect to the gap between the blade and the build platform. It has been clearly shown that the gap needs to be larger than the upper bound of the distribution of powder particles diameter to obtain a high-density powder bed. The DEM simulation indicated that the blade can sweep even powder particles that are not in direct contact with the blade when the powder particles are in a close-packed tetragonal configuration. This is the probable reason for the experimental fact that powder particles smaller than half of the gap are suitable for PBF. This Paper was Originally Published in Japanese in J. JILM 72 (2022) 291–297.